Assessment of the median ages at sexual maturation stages of Brazilian schoolchildren according to overweight status and type of school over a 5‐year period: 2007–2012/2013. Issue 4 (12th September 2021) - Matsuo, Luísa Harumi; Adami, Fernando; Silva, Diego Augusto Santos; de Assis Guedes de Vasconcelos, Francisco; Longo, Giana Zarbato; Schoueri, Jean Henri Maselli; de Fragas Hinnig, Patrícia
Abstract: Objectives: A secular trend of earlier puberty has been observed in girls, and, although more uncertain in boys, is associated with an increasing trend in the prevalence of overweight and obesity. We aimed to compare the median ages of sexual maturation stages in schoolchildren from a city in southern Brazil over a 5‐year period, according to weight status and type of school. Methods: Two cross‐sectional studies were performed in 2007 and 2012/2013, including 2215 and 1614 schoolchildren, respectively. Body mass index z ‐scores were calculated and categorized as either nonoverweight or overweight (including obesity). The type of school was categorized as either public or private. Sexual maturation was self‐assessed according to the Tanner stages. Mann–Whitney and Kruskal–Wallis tests were performed to compare the median ages of sexual maturation stages. Results: The median age decreased for almost all stages over the 5‐year period in both sexes. In boys, the decrease ranged from 0.3 to 1.0 years (stages 2, 3, 4, and 5 for genitalia, and stages 2 and 4 for pubic hair), and from 0.3 to 0.7 years (stages 2, 3, and 4 for breast, and stages 3, 4, and 5 for pubic hair). In 2012, overweight students had lower median ages for most stages compared to those in 2007, especially in girls. Differences by type of school were balanced across years. Conclusions: The median age of Tanner's stages after 5 years was reduced in both sexes. In overweight girls, the reduction was more pronounced. The results by type of school were inconsistent.